Silencing GOLGA8B inhibits cell invasion and metastasis by suppressing STAT3 signaling pathway in lung squamous cell carcinoma. Issue 11 (17th June 2022) - Li, Zhanzhan; Li, Yanyan; Li, Na; Shen, Liangfang; Liu, Aibin
Abstract: Changes to some Golgi subfamily member proteins are reported to be involved in tumor metastasis. However, the functional role and potential mechanism of the Golgi A8 family member B (GOLGA8B) in lung squamous cell carcinoma (LUSC) remains unknown. In the present study, GOLGA8B expression was detected using qRT-PCR, Western blot, and immunohistochemistry (IHC). In vivo animal experiments and in vitro functional assays were performed to explore the function of GOLGA8B in LUSC. Luciferase assays were performed to investigate the underlying targets of GOLGA8B in LUSC. GOLGA8B was shown to be highly expressed in LUSC metastasis tissue, and significantly associated with the distant metastasis-free survival of LUSC patients. Loss-of-function assays indicated that silencing GOLGA8B suppressed LUSC cell tumorigenesis in vivo and weakened in vitro invasion and migration. GOLGA8B silencing-induced inhibition of invasion and migration was associated with the inactivation of STAT3 signaling. Importantly, these results showed that the number of circulating tumor cells (CTCs) was markedly higher in the GOLGA8B silencing group than in the control vector group. GOLGA8B expression was positively associated with p-STAT3 expression in LUSC tissue. Study findings revealed a novel mechanism by which GOLGA8B promotes tumor metastasis in LUSC cells and suggests that this protein could be a promising target for antitumor metastasis therapy in LUSC patients.